Parents' Perceptions Regarding Fulfilling Children's Nutritional Needs According to the Contents of My Plate in Pujon District - Afifah, Azzah; Hayyu Erfantini, Imro’atul (Journal of Nutrition and Public Health, 2026)
Background:Providing adequate nutrition for early childhood is crucial for optimal growth and development. The government has strived to improve nutritional quality through the "Isi Piringku" (My Plate) guidelines, which emphasize balanced intake of carbohydrates, protein, and vegetables and fruit. In this context, parental perception is key, as they are fully responsible for providing and managing their children's daily meals. Aims:This study aims to determine the level of parental perception in fulfilling children's nutritional needs based on the "Isi Piringku" guidelines in the Pujon District area. Methods:This study used a quantitative approach with a descriptive research design. Subjects included 67 parents from four villages in Pujon District: Ngabab, Pandesari, Bendosari, and Pujon Kidul. Data were collected using a questionnaire and analyzed using percentage analysis. Result: The research results show that parents in Pujon District generally have low perceptions regarding children's nutritional needs according to the "Isi Piringku" guidelines. While basic understanding of food portion sizes is quite good, specific weaknesses remain in understanding micronutrients and the classification of certain types of food. Conclusion: The study concluded that although parents understand the importance of a balanced diet, their daily implementation is not optimal. Therefore, more intensive, structured, and sustainable efforts are needed to improve nutrition education for parents to achieve ideal child nutrition in Pujon District.